1997
DOI: 10.1096/fasebj.11.13.9367347
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the potential carcinogenicity of 60 Hz linear sinusoidal continuous‐wave magnetic fields in Fischer F344 rats

Abstract: Electric and magnetic fields (EMFs) associated with the production, transmission, and use of electricity are ubiquitous in industrialized societies. These fields are predominantly of low frequency (50/60 Hz) and are generally of low intensity. Review of the epidemiological evidence shows that the association between exposure to EMFs and cancer is weak and inconsistent, and generally fails to show a dose-response relationship. Moreover, in view of the methodological problems of these epidemiological studies, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
2
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 26 publications
5
33
2
1
Order By: Relevance
“…However, when considered together, long-term exposure of rodents to power frequency magnetic fields that are 5,000-to 10,000-fold (the present study), 10,000-to 20,000-fold (30), and 50,000-to 100,000-fold (56) higher than field levels that are routinely encountered in residential environments has demonstrated no pattern of increased cancer risk. These data, when considered as a whole, provide little or no evidence that exposure to pure 60 Hz linear magnetic fields at up to 10 G field intensities for up to 2 yr can affect neoplastic development in the F344/N rat.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…However, when considered together, long-term exposure of rodents to power frequency magnetic fields that are 5,000-to 10,000-fold (the present study), 10,000-to 20,000-fold (30), and 50,000-to 100,000-fold (56) higher than field levels that are routinely encountered in residential environments has demonstrated no pattern of increased cancer risk. These data, when considered as a whole, provide little or no evidence that exposure to pure 60 Hz linear magnetic fields at up to 10 G field intensities for up to 2 yr can affect neoplastic development in the F344/N rat.…”
Section: Discussioncontrasting
confidence: 58%
“…In the Linet study, however, a small increase in risk for childhood leukemia was seen in residential exposures of about 3 mG (28). At (30). Similarly, a Japanese study involving exposure of male and female F344 rats to 50 Hz magnetic field strengths of up to 50 G for 2 yr was also negative for any correlation between exposure and cancer incidence (56).…”
Section: Discussionmentioning
confidence: 89%
“…Using different exposure protocols, Yasui et al (1997) reported no differences in leukemia or lymphoma incidences in rats exposed to either 500 µT or 5,000 µT (5 or 50 G). Likewise, Mandeville et al (1997) reported no effects on the incidence of leukemia in female rats exposed to 2, 20, 200, or 2,000 µT (0.02, 0.2, 2, or 20 G). Finally, Babbitt et al (2000) saw no differences in total hematopoietic neoplasms or lymphomas in female mice exposed to 1,400 µT (14 G) (circularly polarized) EMFs.…”
Section: Animal Carcinogenicity Studies With Emfsmentioning
confidence: 97%
“…Three large-scale, long-term studies of EMF exposure have been conducted in rats Mandeville et al 1997;Yasui et al 1997) and two in mice (Babbitt et al 2000;McCormick et al 1999). Descriptions and findings from these investigations are summarized in Table 2.…”
Section: Animal Carcinogenicity Studies With Emfsmentioning
confidence: 99%
“…En expérimentation animale, les études d'initiation (Mandeville et al, 1997 ;Yasui et al, 1997 ;McCormick et al, 1998McCormick et al, , 1999 et de promotion tumorale (Bernard et al, 2008 ;SCENIHR, 2009SCENIHR, , 2013, qui n'ont pas montré d'effet du champ magnétique, s'intègrent dans cette analyse.…”
Section: La Question Des Leucémies De L'enfantunclassified